Effects of Acute Ammonium Nitrate Levels Caused by Agricultural Activities on Four Amphibian Species in The Eastern Black Sea Region - Handan Karaoglu (Turkish Journal of Agriculture: Food Science and Technology)
The tadpoles of four amphibian species, namely the Marsh Frog (Pelophylax ridibundus), the Iranian Long-Legged Frog (Rana macrocnemis), the Caucasian Parsley Frog (Pelodytes caucasicus) and the Variable Green Toad (Bufotes variabilis), were exposed to acute concentrations (0 to 500 mg/L) of ammonium nitrate to assess the lethal effects (larval growth, abnormalities, mortality, and LC50 values). Eggs of each species were obtained from clean and polluted habitats in the same region and the tadpoles for experiments were provided from those eggs in the laboratory conditions. Although there was some variability between different populations of the same species or between different species in the observed effects, acute levels of ammonium nitrate caused decreased growth rate and increased abnormalities and mortality in general. Among the 4 amphibian species, the Variable Green Toad was the most damaged one in terms of growth reduction (on average 77-83%), and abnormality rates, and the most damaged one in terms of mortality rates was the Marsh Frog (on average 61-72%). Additionally, the species with the lowest concentration of ammonium nitrate, which killed half of its population, was the Marsh Frog. LC50 values for two populations of Marsh Frog were 37 and 59 mg/L. As a result of our research, it was determined that the acute fertilizer levels caused by agricultural activities in the region had very important harmful effects for all the species we examined. In this context, it can be said that very important environmental and biodiversity problems may occur if certain precautions are not taken regarding the use of the fertilizers and if the awareness of the farmers using these fertilizers cannot be raised.